SURGICAL TREATMENT OF ACUTE APPENDICITIS IN PREGNANCY (British Journal of Global Ecology and Sustainable Development, 2023)
The article was investigated occurring acute appendicitis in pregnancy, clinical signs and the best methods of diagnosis and treatment.